2003
DOI: 10.1007/s00439-003-0974-9
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the human FATE gene in 144 infertile men

Abstract: The FATE gene maps to Xq28 where one case of a translocation breakpoint has been found in an infertile man. Moreover, the FATE promoter contains a putative SF-1-binding site, and FATE has been proposed as representing a target gene of SF-1 in testicular development or germ cell differentiation. This study presents a complete mutational screening of the FATE gene in a random group of 144 infertile males. Four polymorphisms and two mutations were found. Three of the polymorphisms, viz., 741C-->T, 905A-->C, and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In detail, we have identified several interesting DEGs in Sertoli cells ( including INHA, BEX1, GSTA1, DEFB119, and FATE1) and MIX (including CD63, TIMP1, PTGDS, and INSL3) from this NOA patient as compared with those in donors with normal spermatogenesis (Figures 7E and 7F). Many of these genes were potentially associated with male reproduction (Olesen et al, 2003;Yang et al, 2002). And GO terms, such as ''response to oxidative stress'' and ''DNA damage response,'' were enriched in the upregulated genes of the testicular somatic cells from this NOA patient ( Figure 7G).…”
Section: Scrna-seq Data Of Human Spermatogenesis As a Reference For Tmentioning
confidence: 99%
“…In detail, we have identified several interesting DEGs in Sertoli cells ( including INHA, BEX1, GSTA1, DEFB119, and FATE1) and MIX (including CD63, TIMP1, PTGDS, and INSL3) from this NOA patient as compared with those in donors with normal spermatogenesis (Figures 7E and 7F). Many of these genes were potentially associated with male reproduction (Olesen et al, 2003;Yang et al, 2002). And GO terms, such as ''response to oxidative stress'' and ''DNA damage response,'' were enriched in the upregulated genes of the testicular somatic cells from this NOA patient ( Figure 7G).…”
Section: Scrna-seq Data Of Human Spermatogenesis As a Reference For Tmentioning
confidence: 99%
“…There is no evidence that MFF or other mitochondrial fission factors are important for male fertility in humans. Fetal and adult testis-expressed 1 (FATE1) is a testis-specific protein with some sequence similarity to MFF (Olesen et al, 2001), but its role in human fertility remains inconclusive (Olesen et al, 2003).…”
Section: The Emerging Role Of Mitochondrial Dynamics During Spermatogmentioning
confidence: 99%
“…FATE1 belongs to the CTA family, and in 2003 it was sequenced in a cohort of 144 randomly selected infertile patients (Olesen et al 2003). The authors reported two missense variants in two unrelated asthenozoospermic men.…”
Section: Fate1mentioning
confidence: 99%